Cohesin acetylation and ATPase activity control cohesion and loop architecture through distinct mechanisms - Lorenzo Costantino; Tiantian Ye; Kevin Boardman; Siheng Xiang; Jonathan Luo; Yudi Mu; Wenxiu Ma; Douglas Koshland (Proceedings of the National Academy of Sciences, 2026)
Cohesin is a conserved protein complex that mediates sister chromatid cohesion, chromosome condensation, gene regulation, and DNA repair. These processes rely on cohesin’s ability to tether DNA and form chromatin loops, which depend on cohesin’s ATP hydrolysis activity and Eco1-mediated acetylation of two lysines (K112 and K113 in budding yeast) in its Smc3 subunit. However, how cohesin’s ATPase activity and acetylation integrate to control cohesin functions in vivo remains poorly understood. To address this, we analyzed chromatin architecture in yeast mutants with altered cohesin acetylation, and/or ATPase activity. Single K112 or K113 acetyl-null mutants retained wild-type loop length distributions and positioned loops at cohesin-associated regions (CARs), suggesting acetylation of either lysine alone is sufficient for loop positioning. Conversely, Eco1 depletion (removing both acetylations) led to extended loops and loss of positioned loops, despite unchanged cohesin binding. We found that a cohesin acetylation mutant lacking the tethering activity required for cohesion could form positioned loops like the wild type, whereas cohesion-competent mutants lacked positioned loops. Together, these results support a model in which cohesin’s activities required for cohesion and loop formation are mechanistically separable, arguing against a passive loop-capture mechanism. K112 acetyl-mimic mutant partially reduced ATPase activity, yet showed wild-type loop profile, suggesting that lowering ATPase activity does not dictate loop positioning. However, hyper-ATPase mutants exhibited fewer random loops and more positioned loops, indicating that elevated ATPase promotes loop stabilization. Together, these results indicate that acetylation fine-tunes cohesin ATPase activity and function to shape genome architecture.